PENGARUH KELAS IBU HAMIL TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG INISIASI MENYUSU DINI - Rully Fatriani (Jurnal Kesehatan Panca Bhakti Lampung, 2018)
The antenatal class is cooperative learning for pregnant women to increase knowledge, change attitude and practice. One of antenatal class material is early breastfeeding initiation. This research aims to know antenatal class effect on pregnant women knowledge and attitude about early breastfeeding initiation.This type of quasi experimental research design with control group pretest-posttest was used towards 52 pregnant women divided into two groups; attending antenatal class and not attending antenatal class using simple random sampling. Interview was conducted to measure knowledge and attitude about early breastfeeding initiation, mother practice was observed during delivery. Data analysis using chi-square test. The result showed that mothers with good knowledge were increasing from 30,8 % to 100 % after participating in antenatal class. The antenatal class significantly changed attitude about early breastfeeding initiation (p value = 0,034). The antenatal class was found to be effective in changing maternal knowledge and attitude about early breastfeeding initiation. Midwives are recommended to optimize antenatal class performance to increase early breastfeeding initiation rate. Policy holder also expected to pay attention towards antenatal class implementation in working region with low rate of early breastfeeding initiation